Multimodalidade e atenção conjunta na construção de um almanaque digital no 6º ano do ensino fundamental público em Camaragibe-PE. - Carvalho, Marcia Antonia de Souza (2023)
The school, as a place of learning, encourages and makes possible the reflection of how the language skills of the subjects are realized in the construction of their knowledge, therefore, this dissertation had as main objective to investigate the process of multimodal referencing of children of the 6th year of Elementary School final years, in scenes of joint attention, during the collaborative activity of producing a digital almanac. We adopted the multimodal perspective, in which gesture and speech are part of the same linguistic-cognitive system, as advocated by McNeill (2014) and Kendon (1981, 2009, 2019); supporting us in the discussions on Multimodal Envelope by Ávila-Nóbrega (2010, 2017); and in studies on joint attention by Tomasello (1999, 2019), Costa Filho (2016), among others. We carried out a qualitative action-research regarding the multimodal functioning of language in joint attention interactions between 10 and 12-year-old children from a state school in Camaragibe. The research was based on a case study of three groups, each comprising three children. The research stages were: (i) Presentation of the work Morte e vida Severina and the almanac (ii) holding meetings with activities about the work, in an interdisciplinary relationship, (iii) production of a digital almanac about the work. During the development period of the activity, the students' engagement in collaborative work situations and their vocal productions, gestures and eye movements in joint attention scenes during the elaboration of the digital almanac were observed. Data were collected in nine meetings, with a digital camcorder, we analyzed a total of six clippings related to the three groups, each filming of the nine meetings, had an average of 30 minutes of recording, the data are stored in external HD and own notebook of the researcher. For data transcription, we considered the following steps: (i) choice of excerpts for transcription, we adopted the criterion of the presence of joint attention; (ii) transcription of the selected data, using the ELAN software, which allows simultaneous audio and video transcription. The data analysis, carried out qualitatively and quantitatively, highlights the composition of several Multimodal Envelopes in a mixture of gestural planes, look and vocal production and the referencing process that occurred through the relationship of repetition and reiteration, in addition to the strategy of resuming and the direction of the scene in the interactive engagement. The deictic gesture was the one that most occurred in the interactive scenes, followed by the iconic gestures and gesticulation. The most recurrent type of gaze direction was the look of accompaniment and sharing of expectation. This work made it possible to understand the relationship between joint attention, multimodal referencing and technology during the activity of creating the digital almanac, providing relevant information about the role of students in shared engagement during this collective production.